The Berkeley-Haas School of Business : codifying, embedding, and sustaining culture - Chatman, Jennifer (SAGE Knowledge. Cases., 2017)
The Berkeley-Haas School of Business case study outlines the history of Dean Rich Lyons' culture efforts. The case discusses the challenges the dean faced as well as future challenges to sustain the culture after the dean steps down at the end of the 2017/2018 school year.